Low energy models of string theory - Tadros, Poula (My University, 2022)
String theory is the prime candidate of the theory of everything. However, it must be defined in ten dimensions to be consistent. To get 4D physics, the 6 other dimensions should be curled up in a small compact manifold, this procedure is called string compactification. In this thesis, we will review different compactification schemes proving that in absence of flux, the compact manifold must be a Calabi Yau manifold. Then, we review compactifications with flux using generalized complex geometry. We then discuss some applications in cosmology like the swampland project and the cosmological models derived from it. Finally, we discusssome open questions in the field.
Keywords: String compactifications, Flux compactifications, The swampland project